Implementation of TPACK in STEAM-Based Chemistry Learning in Higher Education: A Bibliometric Analysis - Evi Sapinatul Bahriah; Etin Solihatin; Ivan Hanafi (Proceeding International Conference on Digital Education and Social Science, 2024)
Students in the era of industrial revolution 4.0 and society 5.0 must have good competence and skills. Therefore, the implementation of Technological Pedagogical Content Knowledge (TPACK) in STEAM (Science, Technology, Engineering, Art, and Mathematics) Education is very suitable to be adapted in basic chemistry learning in higher education. Therefore, this study aims to find out research trends related to implementation TPACK in STEAM-Based Chemistry learning in higher education. The method used is Systhematic Literatute Review. The data collection technique used was to conduct research studies for the last 9 years (2014-2024) according to the keywords. The inclusion and exclusion criteria for article search include TPACK, STEAM Education, STEAM-based learning, chemistry learning, STEAM in higher education, etc. The research data obtained were analyzed using a bibliometric approach with the help of the VOSviewer program. This study based on Google Scholar. The results of the study show many research trends related to TPACK in STEAM-based chemistry learning. The integration of TPACK in STEAM-based chemistry learning is generally effective in improving the learning process and learning outcomes. Therefore, it is necessary to adapt and further modify STEAM-based learning, especially in basic chemistry learning at higher education.